Analisis Pengaruh Profesionalisme Dan Komitmen Organisasi Terhadap Kinerja Pegawai Kantor Pencarian Dan Pertolongan Di Ambon - Tutupoho, Saleh; Tamher, Etvin R.; Sangur, Korneles; Liur, Lisye Magdalena; Hiariej, Dewi S. (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to analyze the influence of professionalism and organizational commitment on employee performance. The sample used in this study was 100 employees at the Ambon Search and Rescue Office. The data analysis method used is multiple regression analysis. The results showed that professionalism was positive and significant to employee performance. Furthermore, the results also show that the organization's commitment is positive and significant to employee performance.